A Randomized Controlled Trial on Analgesic Effects of Intravenous Acetaminophen versus Dexamethasone after Pediatric Tonsillectomy - Faiz, Seyed Hamid Reza (Kowsar, 2013)
BACKGROUND: A few studies are available actually comparing the clinical efficacy of intravenous acetaminophen with other medications such as dexamethasone to inhibit postoperative adverse events in children. OBJECTIVES: This randomized blinded controlled trial was designed to compare controlling status of postoperative events in children after tonsillectomy randomized to receive either intravenous acetaminophen or dexamethasone. PATIENTS AND METHODS: Eighty four children aged between 4 to 13 undergoing tonsillectomy were randomized using a computer-generated schedule to double-blind treatment with intravenous acetaminophen (15 mg/kg) or intravenous dexamethasone (0.1 mg/kg). Children were post-operatively assessed for swallowing pain, pain while opening mouth, ear pain, and postoperative sore throat in recovery room (within one hour after surgery), at the time of admission to the ward, as well as at 12 and 24 hours after surgery, assessed by the objective pain scoring system (OPS; minimum score: 0 = no pain, maximum score: 10 = extreme pain). RESULTS: There were no significant differences between the two groups with regard to the severity of postoperative pain due to swallowing or opening mouth measured at the different study time points from postoperative recovery to 24 hours after the surgery. There was no difference in ear pain severity at the time of postoperative recovery, at the admission time to ward and also at 12 hours after surgery; however mean score of ear pain severity was significantly higher in those who administered acetaminophen 24 hours after operation. Also, the mean score severity of sore throat was significantly higher in the acetaminophen compared with the dexamethasone group within 12 hours of surgery. Postoperative vomiting and bleeding were similarly observed between the two study groups. The severity of swallowing pain, pain while opening mouth, ear pain, as well as postoperative sore throat as gradually assuaged within 24 hours of tonsillectomy in both groups, however no between-group differences were observed in the trend of the severity of these events. CONCLUSIONS: The dexamethasone-based regimen may have more advantage over the intravenous acetaminophen regimen for inhibiting pain and PONV following tonsillectomy in children.